2023
DOI: 10.3389/fmicb.2023.1160736
|View full text |Cite
|
Sign up to set email alerts
|

Single-nucleotide resolution detection of Topo IV cleavage activity in the Escherichia coli genome with Topo-Seq

Abstract: Topoisomerase IV (Topo IV) is the main decatenation enzyme in Escherichia coli; it removes catenation links that are formed during DNA replication. Topo IV binding and cleavage sites were previously identified in the E. coli genome with ChIP-Seq and NorfIP. Here, we used a more sensitive, single-nucleotide resolution Topo-Seq procedure to identify Topo IV cleavage sites (TCSs) genome-wide. We detected thousands of TCSs scattered in the bacterial genome. The determined cleavage motif of Topo IV contained previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 79 publications
3
4
0
Order By: Relevance
“…8). This periodic nucleo�de bias is consistent with, albeit slightly weaker than, in vivo end-sequencing measurements of gyrase and topo IV cleavage sites and has been associated with the length of DNA gyrase wraps around its CTD 19,20 .…”
Section: Gyrase and Topo IV Exhibit Similar But Dis�nct Cleavage Site...supporting
confidence: 77%
See 4 more Smart Citations
“…8). This periodic nucleo�de bias is consistent with, albeit slightly weaker than, in vivo end-sequencing measurements of gyrase and topo IV cleavage sites and has been associated with the length of DNA gyrase wraps around its CTD 19,20 .…”
Section: Gyrase and Topo IV Exhibit Similar But Dis�nct Cleavage Site...supporting
confidence: 77%
“…In addi�on to the effects of quinolones, we found that gyrase and topo IV have dis�nct enzymespecific cleavage site-specifici�es. Although previous in vitro and in vivo studies have found differences in gyrase and topo IV cleavage paterns 16,20 , they have only been compared in the presence of quinolones. Given that quinolones have differen�al effects on gyrase and topo IV 50 , these effects could have accounted for the apparent difference in their cleavage paterns.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations